Livestock receptivity and stocking rate in differents micro-regions of La Pampa Province (Argentine) and its relation to rainfall (Semiárida, 2018)
In the semi-arid region of central Argentina, apart of which is included in La Pampa province, most of the land is dedicated to livestock activity, mainly cattle breeding on grass-lands as the primary source of fodder. Stocking rate in these environments does not always keep an adequate relationship with carrying capacity to prevent degradation of these ecological systems. Rainfall levels play a key role for both, the geographical layout of plantcommunities and variability in forage production and availability between and within years. Rangeland carrying capacity for livestock in such a region would be closely related to rainfall and land background of use, major determinants of the state of condition and forageproduction of plant communities. The present work was aimed to: (a) assess how forageavailability and carrying capacity of different types of plant community units and micro-regions of La Pampa relates to rainfall; and (b) construct maps showing data for those threevariables in sites of La Pampa under different conditions of ecosystems. There were considered all the plant community units that make up the target region, two rangeland condition states (good and fair) and three climatic scenarios of different rainfall levels (good, higher than 120% of annual mean value; normal, within mean value +20%; and poor, lowerthan 80% of mean value). Estimation of carrying capacity was based on pre-existing data of forage availability for each site. It was noted that both forage availability by plant community unit and carrying capacity by micro-region are strongly explained by rainfall level. Besides, a close relationship was observed between actual stocking rate and the estimated carrying capacity when rangeland condition was fair with years of normal and good rainfall. In years of poor rainfall, regardless of the rangeland condition state, forage availability is not enough to sustain the stock of cattle at the historical level for the province. In order toassure the conservation of natural resources and achieve a sustainable livestock production, it is imperative to follow models that consider both the productive capacity and variability for each region of the province, attributes that are instead strongly influenced byecological characteristics.
Keywords: Pampean semiarid region; Rainfall; Stocking rate; Carrying capacity; Grasslands